Collaboration in early childhood services: Trends and patterns from a bibliometric study - Ebni Sholikhah; Siti L. Mubasiroh; Maryani Maryani (South African Journal of Childhood Education)
Background: Collaboration in early childhood services is essential for integrating interdisciplinary efforts to support child development. Despite its importance, research trends in this area remain fragmented and require systematic mapping.